Resposta :
Resposta:
[tex]\textsf{Leia abaixo}[/tex]
Explicação passo a passo:
[tex]\mathsf{y = x^2 - 3x - 4}[/tex]
[tex]\mathsf{x^2 - 3x - 4 = 0}[/tex]
[tex]\mathsf{\Delta = b^2 - 4.a.c}[/tex]
[tex]\mathsf{\Delta = (-3)^2 - 4.1.(-4)}[/tex]
[tex]\mathsf{\Delta = 9 + 16}[/tex]
[tex]\mathsf{\Delta = 25}[/tex]
[tex]\mathsf{x = \dfrac{-b \pm \sqrt{\Delta}}{2a} = \dfrac{3 \pm \sqrt{25}}{2} \rightarrow \begin{cases}\mathsf{x' = \dfrac{3 + 5}{2} = \dfrac{8}{2} = 4}\\\\\mathsf{x'' = \dfrac{3 - 5}{2} = -\dfrac{2}{2} = -1}\end{cases}}[/tex]
[tex]\boxed{\boxed{\mathsf{S = \{4;-1\}}}}[/tex]
Resposta:
Explicação passo a passo:
∆ = (-3)² -4.1.(-4) = 9 +16=25 => √∆=5
x= 3±5/2
X'= 8/2 = 4 ✓
X"= -2/2= -1 ✓